1999
DOI: 10.1029/1999gl010689
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic evolution and acceleration of the solar wind

Abstract: Abstract. We investigate the effects of kinetic waveparticle interactions on the solar wind using a global hybrid model. The model follows the evolution of the particle distributions along an inhomogeneous field line under the influence of wave-particle interactions, an ambipolar electric field that is consistent with the particle distributions themselves, and Coulomb collisions. This represents the "first results" of global evolutionary study of the solar wind that take into account these kinetic effects. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 22 publications
1
56
1
Order By: Relevance
“…(5), we assume that the inward propagating waves constitute only 2.4 × 10 −6 of the total wave power at 1 R (solar radius). Even with such a small ratio of e − /e + near the corona, the presence of these sunward propagating waves have been shown to lead to double-peaked proton velocity distributions in the solar wind (Tam & Chang 1999a). The reason for the formation of the non-thermal feature is as follows.…”
Section: Ion Cyclotron Resonant Heatingmentioning
confidence: 99%
See 3 more Smart Citations
“…(5), we assume that the inward propagating waves constitute only 2.4 × 10 −6 of the total wave power at 1 R (solar radius). Even with such a small ratio of e − /e + near the corona, the presence of these sunward propagating waves have been shown to lead to double-peaked proton velocity distributions in the solar wind (Tam & Chang 1999a). The reason for the formation of the non-thermal feature is as follows.…”
Section: Ion Cyclotron Resonant Heatingmentioning
confidence: 99%
“…Therefore, in general, more wave power is available to the helium ions than to the protons, at least in the observed regimes (0.3-1 AU). Extrapolating the power spectrum to distances close to the sun, Tam & Chang (1999a) have shown that the kinetic waveparticle interactions in general transfer more energy to a helium ion than to a proton. Although the energy is mainly transferred into the transverse direction, it converts into the field-aligned direction downstream in the solar wind due to the mirror effect, leading to a preferential acceleration of the helium ions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30 However, kinetic approaches to the study of the solar wind plasmas which include the charged dust particles as one of the plasma components are not easily found. That was one of the motivations of our recent publications on the subject of dusty plasmas, particularly of Ref.…”
Section: Introductionmentioning
confidence: 99%